Organisational behaviour an introduction - Cross, Christine; Carbery, Ronan (Red Globe Press, 2021)
This lively and comprehensive introduction to organisational behaviour demonstrates how research into human behaviour can be applied in the workplace. It assumes no prior work experience, instead asking students to draw on everyday occurrences and complete a range of engaging activities to deepen their understanding of key topics such as personality, perception and motivation. With a focus on helping students to develop key skills useful to future employers, it offers a wealth of real-world examples, coverage of contemporary issues, and an international approach.